Cultura organizacional para mejorar la gestión de recursos humanos en la empresa Piangesa - Chicama - Salazar Franchini, Billy Jack (2012)
The present study was intended primarily to emphasize the importance of organizational culture as a determining factor in the effectiveness of human resource management in PIANGESA Industrial Company. For the development of the aforementioned title, consideration was given to the management of the terms used in the race, the cultural elements that influence the effectiveness of staff and the relationship of the elements identified with the development of the dominant culture that should see organizational climate reflected in a motivating, challenging and participative. Two or three decades ago Human Resource was defined simply as one that provided the workforce to an organization. This definition has evolved and is now considered to Human Resources as the study that helps organizations to obtain, develop, maintain and retain the right number and type of employees. Another modern definition concisely points out that Human Resource Management involves all management decisions and practices that affect and influence people, now Human Resources are now regarded as a key element in the development of enterprises, allowing the realization of these goals by raising his role to a strategic position. Adding to this definition the term the importance of organizational culture as booster success in organizations and a strategic tool that must be considered by the company to achieve high levels of productivity and above all improve the quality of care provided. This research was conducted through a literature review and application of the various public surveys as part of the institution, with reference to the theoretical part of this study was developed as a non-experimental, descriptive and correlational. The study hypothesis was determined as follows: If there is a relationship between organizational culture and improving the management of Human Resources in Business Industrial PIANGESA. It was concluded that culture guides all administrative processes of the institution and is a crucial factor in improving the management of human resources of the company.